Regulatory Governance and Sector Performance : Methodology and Evaluation for Electricity Distribution in Latin America - Andres, Luis; Guasch, José Luis; Lopez Azumendi, Sebastián (World Bank, Washington, DC, 2012)
This paper contributes to the literature that explores the link between regulatory governance and sector performance. The paper develops an index of regulatory governance and estimates its impact on sector performance, showing that indeed regulation and its governance matter. The authors use two unique databases: (i) the World Bank Performance Database, which contains detailed annual data for 250 private and public electricity companies in Latin America and the Caribbean; and (ii) the Electricity Regulatory Governance Database, which contains data on several aspects of the governance of electricity agencies in the region. The authors run different models to explain the impacts of change in ownership and different characteristics of the regulatory agency on the performance of the utilities. The results suggest that the mere existence of a regulatory agency, regardless of the utilities' ownership, has a significant impact on performance. Furthermore, after controlling for the existence of a regulatory agency, the ownership dummies are still significant and with the expected signs. The authors propose an experience measure in order to identify the gradual impact of the regulatory agency on utility performance. The results confirm this hypothesis. In addition, the paper explores two different measures of governance, an aggregate measure of regulatory governance, and an index based on principal components, including autonomy, transparency, and accountability. The findings show that the governance of regulatory agencies matters and has significant effects on performance.